Reviewing Specific Grant in 2015-2019 Period: Consistency and Quality Matters - Agus Manshur (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2020)
Specific Grant hereinafter referred to as Dana Alokasi Khusus (DAK) are funds sourced from APBN revenues allocated to certain regions with the aim of helping to fund specific activities which are local government affairs and in accordance with national priorities. Based on PP 55/2005 Article 50 Paragraph 1, the amount of DAK is determined annually in the APBN. Furthermore, Article 50 Paragraph 2 clarifies the basis for the allocation of DAK in which DAK is allocated in the APBN in accordance with programs that are of national priority. Again, in Article 52 Paragraph 1, the definition of the program is clarified, that is, programs that become national priorities are contained in the Government Work Plan (RKP) of the fiscal year concerned.